P1463Regional variation in survival rates among primary prevention implantable cardioverter-defibrillator recipients in Eastern and Northern Europe POLKARD Polish ICD Registry perspective. (18th June 2020) - Warchol, I; Lubinski, A; Sterlinski, M; Kowalski, O; Goscinska-Bis, K; Pytkowski, M; Mitkowski, P; Kazmierczak, J; Szwed, H; Przybylski, A; Trusz-Gluza, M; Kempa, M; et al.
Abstract: Funding Acknowledgements: None. OnBehalf: POLKARD Polish ICD Registry Objective: The findings of Danish Study to assess the efficiency of ICD in patients with non ischemic heart failure has recently raised questions about the current strategy of ICD implantation for the primary prevention of sudden cardiac death. POLKARD - Polish ICD Registry is a prospective, non-randomised, central registry of patients who are referred for an implantation of an ICD in Poland. The Registry contains prospectively collected follow-up data including mortality. Purpose: To compare survival rates between Polish and Danish 'real-world' non-ischemic primary prevention cohorts. Methods: Retrospective analysis of clinical characteristics and long-term follow-up of patients referred for primary prophylactic implantable cardioverter defibrillator (ICD) implantation in Poland between April 2008 and November 2014 was performed. The primary outcome of the trial was all-cause mortality. Results: The polish study cohort was large (964) as compared to Danish population randomized to receive ICD therapy (556). The median follow-up time in DANISH Study and Polish ICD Registry was 67, 6 and 77 months, respectively. Compared with patients enrolled in the DANISH Study, patients in the Polish ICD Registry were age-similar. However, the polish study population was male-dominated. What is more, male gender was identified as a risk factor for long-term mortality in polish study population (p = 0.005). In the matched cohorts, there was difference in survival between DANISH Study and Polish ICD Registry patients (all-cause mortality rates: 21, 6% - 44 events per 1000 person-years and 39, 3% - 72 events per 1000 person-years, respectively). Conclusions: Our findings imply that survival among patients who receive a primary prevention ICD for non-ischemic cardiomyopathy in clinical practice in Central Europe is different from Northern Europe.